Parenting of mothers of children in early childhood during the COVID-19 pandemic: qualitative research - Ricardo Barros Gurgel; Juliane Lima Pereira Da Silva; Estela Maria Leite Meirelles Monteiro; Suzana Lins da Silva; Tereza Rebecca de Melo e Lima; Maria Wanderleya de Lavor Coriolano-Marinus (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to understand practices of mothers of children in early childhood who live in contexts of poverty in the face of the COVID-19 pandemic. Methods: an exploratory, descriptive and qualitative study. Participants were selected in the community context, composing an intentional sample to be collected through semi-structured online interviews. Data were analyzed inductively and anchored in the Bioecological Model of Human Development. Results: eight mothers participated in the research. Mothers highlighted pleasure in taking care of their children, although they were overloaded with activities and comprehensive care at the time of the pandemic. Children, in mothers' perception, showed a higher frequency of challenging behaviors, which may be related to negative parenting practices, such as punishment and physical violence. Final Considerations: interventions to support parenting become urgent in the face of changes brought about by the COVID-19 pandemic in families living in a context of poverty.